Synthesis of Microgel Sulfated Carboxymethyl Cellulose (SCMC) by Double Crosslinked Alginate from Lindur Fruit (Bruguiera gymnorrhiza) for Diabetic Ulcer Healing - Hutapea, Jobin Armando; Zaki, Nesfitra Dzakwan; Syahrum, Silvina Faradilla; Putra, Surya Andika; Marbun, Sarah Aknesia; Tarigan, Indra Lasmana (Jurnal Rekayasa Kimia & Lingkungan, 2025)
Microgels have been recognized as promising scaffolds for diabetic wound care due to their favorable properties in promoting wound healing. This study aims to synthesize a microgel using sulfated carboxymethyl cellulose (SCMC) derived from Lindur fruit (Bruguiera gymnorrhiza) for potential application in diabetic ulcer treatment. The synthesis was conducted through a double-crosslinking reaction, and the resulting microgel was characterized using infrared (IR) spectroscopy, scanning electron microscopy (SEM), and in vivo analysis in male mice (Mus musculus). The results demonstrated that the yield of Ca-alginate isolate ranged from 18.67% to 19.46%, with a purity of 19.5%33.1%, viscosity of 31.1931.46 cP, and stable pH at 7. The Ca-alginate isolate exhibited antioxidant activity at 50 ppm with an inhibition percentage of 22.3%. The modification of SCMC was successfully achieved, as confirmed by the presence of characteristic absorption peaks at 1220 cm (asymmetric SO stretching) and 870 cm (symmetric COS stretching vibrations), indicating successful sulfate group incorporation. The microgel swelling ratio was recorded at 660% for microgel A, 700% for microgel B, and 720% for microgel C, with microgel C exhibiting the highest swelling capacity. In vivo wound healing assessment revealed that microgel C facilitated more rapid wound closure, with wound sizes reducing progressively from 0.9 cm on day 3 to 0.5 cm on day 5, 0.3 cm on day 7, and 0.1 cm on day 14. These findings suggest that SCMC-based microgel with alginate derived from Lindur fruit holds significant potential as an innovative formulation for diabetic wound management